Monitoring the newly qualified nurses in Sweden: the Longitudinal Analysis of Nursing Education (LANE) study - Wallin Lars; Omne-Pontén Marianne; Rudman Ann; Gustavsson Petter J (BMC, 2010)
Abstract Background The Longitudinal Analysis of Nursing Education (LANE) study was initiated in 2002, with the aim of longitudinally examining a wide variety of individual and work-related variables related to psychological and physical health, as well as rates of employee and occupational turnover, and professional development among nursing students in the process of becoming registered nurses and entering working life. The aim of this paper is to present the LANE study, to estimate representativeness and analyse response rates over time, and also to describe common career pathways and life transitions during the first years of working life. Methods Three Swedish national cohorts of nursing students on university degree programmes were recruited to constitute the cohorts. Of 6138 students who were eligible for participation, a total of 4316 consented to participate and responded at baseline (response rate 70%). The cohorts will be followed prospectively for at least three years of their working life. Results Sociodemographic data in the cohorts were found to be close to population data, as point estimates only differed by 0-3% from population values. Response rates were found to decline somewhat across time, and this decrease was present in all analysed subgroups. During the first year after graduation, nearly all participants had qualified as nurses and had later also held nursing positions. The most common reason for not working was due to maternity leave. About 10% of the cohorts who graduated in 2002 and 2004 intended to leave the profession one year after graduating, and among those who graduated in 2006 the figure was almost twice as high. Intention to leave the profession was more common among young nurses. In the cohort who graduated in 2002, nearly every fifth registered nurse continued to further higher educational training within the health professions. Moreover, in this cohort, about 2% of the participants had left the nursing profession five years after graduating. Conclusion Both high response rates and professional retention imply a potential for a thorough analysis of professional practice and occupational health.